Terry Pratchett, joueur de foot - Jerzy Brzozowski (Ksiegarnia Akademicka Publishing, 2017)
Sir Terry Pratchett’s “Unseen Academicals” shows the soccer world, but also the University, both of which are important. The title of the French translation, Allez les mages, is the first example of the naturalization strategy which focuses on football, but erases any hint of the British culture and, consequently, the reader of this translation is unable to see any allusion to the Oxford‑Cambridge old rivalry. Moreover, this strategy destroys the tension between the language of the “gentlemen” of the University and ordinary people, humble servants in the University but big ones in the football world. The rendering of the “cockney” by the Parisian argot is, in fact, Berman’s deforming tendency called vulgarization. In conclusion, the author of this paper believes that the French translator of Pratchett’s book, although very clever ar rendering of puns, took the wrong strategic decision, which his Polish colleague did not.